Investigation of the effect of different materials on convective heat transfer - A. A., Ibrahim; P. L., Chong; V. S., Rajasekharan; M. M., Ali; O. S., Zaroog; A. N., Oumer (Faculty Mechanical Engineering, UMP, 2020)
Conventionally, the study of convection heat transfer merely focuses on the behavior of air flow without considering the conductive effect of the horizontal flat plate. However, it is expected that the conductive effect of the horizontal plate somewhat affects the air flow temperature across the flat plate. Therefore, it is motivated to study the variation of air flow temperature across different materials of flat plate in various time frame. The materials used in this study are aluminium, stainless steel and cast iron. Infrared camera and FloEFD simulation software are used to measure the upper surface temperature of the flat plate. For forced convection, the study is carried out within the range of 103 Re 104 and within the range of 1 × 107 Ra < 2.2 × 107 for natural convection. Flow velocity of 2.3 m/s, 4.1 m/s and 5.2 m/s are used for the forced convection. The results showed that aluminium plate cools down faster than the other two metal plates used in all scenarios. Stainless steel’s temperature goes down faster compared to cast iron. These results were supported by the fact that aluminium has higher heat transfer rate of other metals. For forced convection, the discrepancies of temperatures between experimental and simulation studies are below 10%, which demonstrates that the results are reasonably acceptable. For natural convection, even though the discrepancies between simulation and experimental results on temperature variations are relatively large, the temperatures varied in similar pattern. This indicates that the results are reliable.